Die Tagebücher des Grafen Egbert Belcredi 1850-1894 - Höbelt, Lothar (Böhlau, 2016)
The edition includes the diaries of Count Egbert Belcredi from 1850 until his death in 1894. Belcredi - who was the brother of Austrian Prime Minister Richard Belcredi (1865-67) - was an outspoken Conservative, with links both to the Bohemian States Rights Party and the early Christian Social movement in Vienna.